PRÓTESES BUCOMAXILOFACIAIS COMO TRATAMENTO DE DEFORMIDADES OROFACIAIS (REMUNOM, 2024)
Facial deformities are conditions that can cause significant embarrassment and negatively impact the physical and psychological health of patients, affecting their quality of life and creating challenges in their social and family relationships. The development of maxillofacial prostheses has been essential in offering a solution that not only restores appearance but also returns essential functions, improving patients' well-being and self-confidence. This work presents a classification system for maxillofacial prostheses, highlighting the main types and their specific applications.This study aims to conduct a literature review on the etiology of facial deformities and their treatment with maxillofacial prostheses, identifying the factors that influence the incidence of facial trauma, considering congenital origins, traffic accidents, and physical assaults, and detailing the various types of maxillofacial prostheses and their specific applications. To support this research, an extensive bibliographic review was conducted using the main scientific databases, including Google Scholar, PubMed, SciELO, and LILACS. Research in these databases enabled a comprehensive analysis of the literature, gathering studies that contribute to a clear view of the advancements and challenges in the field of maxillofacial prostheses. It is concluded that rehabilitation using maxillofacial prostheses has become an essential procedure in healthcare and is directly associated with quality of life. Each type of prosthesis has its specificity, and understanding the types of prostheses enables the best possible care for each patient, addressing the problem not only functionally but also restoring self-esteem and contributing to mental health. This is what makes the specialty of maxillofacial prosthetics so important in the social context.